Sacramental Ecclesiology: Adopting Augustine’s Totus Christus for Evangelical Ecclesiology - Avila, Angga (Veritas : Jurnal Teologi dan Pelayanan, 2021)
After the 16th-century reformation, the church was faced with the situation of ecclesiological plurality, both differences in traditions and church divisions into many denominations, including evangelical churches. Despite the fact that the evangelical movement was founded with the primary objective of spreading the gospel, it is devoid of coherence in ecclesiology. Based on Augustine’s idea of totus Christus, this research presents a constructive ecclesiology proposal for evangelical churches. Drawing primarily on Augustine’s notion of totus Christus, and by showing that this idea is central to his theological construction, the author proposes the importance of revisiting the doctrine of totus Christus to create an ecclesiology that links to sacramentology and soteriology. The contribution of this research is to show that the doctrine of totus Christus is more organic and sacramental so that it can become the foundation and aspiration for evangelical churches united as the body of Christ to participate in His redemptive works for the salvation of the world.